Principles of Delay Sensitive Multimedia Data Storage and Retrieval - Gemmell, Jim; Christodoulakis, Stavros (ACM Transactions on Information systems, 1992)
This paper establishes some fundamental principles for the retrievl and storage of delay-sensitive multimedia data. Delay-sensitive data include digital audio, animations, and video. Retrieval of these data types from secondary storage has to satisfy certain time constraints in order to be acceptable to the user. The presentation is based on digital audio in order to provide intuition to the reader, although the results are applicable to all delay-sensitive data. A theoretical framework is developed for the real-time requirements of digital audio playback. We show to describe these requirements in terms of the consumption rate of the audio data and the nature of the data-retrieval rate from secondary storage. Making use of this framework, bounds are derived for buffer space requirements for certain common retrieval scenarios. Storage placement strategies for multichannel synchronized data are then categorized and examined. The results presented in this paper are basic to any playback of delay-sensitive data and should assist the multimedia system designer in estimating hardware requirements and in evaluating possible design choices.